(untitled) (mathematica didactica, 2010)
Modern assessment requires to take into account not only the products but also the process of learning. Learning diaries, portfolios, skills assessment and informative exercises present possible solutions. The portfolio was investigated in a case study to find out under which conditions it is possible to figure out something about the learning process of the pupils. It turned out that the students produced different sorts of texts depending on the questions the teacher asked to introduce them to writing. „Explaining texts“ seemed to be most appropriate because they contained the most process information. Concrete written prompts played a key role to stimulate the pupils to write such texts.